Terrorism-related trauma in Africa, an increasing problem - Maryam Alfa-Wali; Kaji Sritharan; Mira Mehes; Fizan Abdullah; Shahnawaz Rasheed (Springer, 2019)
Global terrorist activities have increased significantly over the past decade. The impact of terrorism-related trauma on the health of individuals in low- and middle-income countries is under-reported. Trauma management in African countries in particular is uncoordinated, with little or no infrastructure to cater for emergency surgical needs. This article highlights the need for education, training and research to mitigate the problems related to terrorism and surgical public health.